2005
DOI: 10.1016/j.jvb.2004.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of career decisional states in adolescence

Abstract: This longitudinal study tested students in Grade 8 and again in Grade 10 on career (maturity, barriers, indecision, decision-making self-efficacy), well-being (self-esteem, life satisfaction, coping) and social (school achievement, paid work experience) variables. Students were allocated to decided or undecided conditions at T1, T2 and across T1-T2, based on self-reported global decidedness ratings. As predicted, the undecided students had poorer career, well-being and social outcomes than the decided students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 34 publications
7
76
1
6
Order By: Relevance
“…First, consistent with the findings of previous studies (Barrett & Tinsley, 1977a, 1977bChartrand et al, 1990;Creed et al, 2005;Germeijs & De Boeck, 2003;Resnick et al, 1970;Saunders, Peterson, Sampson, & Reardon, 2000), we found that self-esteem was negatively related to career uncertainty. Nevertheless, we provided an additional contribution to explain why self-esteem could contribute to career certainty.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, consistent with the findings of previous studies (Barrett & Tinsley, 1977a, 1977bChartrand et al, 1990;Creed et al, 2005;Germeijs & De Boeck, 2003;Resnick et al, 1970;Saunders, Peterson, Sampson, & Reardon, 2000), we found that self-esteem was negatively related to career uncertainty. Nevertheless, we provided an additional contribution to explain why self-esteem could contribute to career certainty.…”
Section: Discussionsupporting
confidence: 92%
“…One important individual difference factor that can explain different levels of career uncertainty across students is self-esteem. Previous research findings consistently suggested that there is a significant and positive link between career indecision and lower self-esteem (Creed, Prideaux, & Patton, 2005;Germeijs & De Boeck, 2002;Santos, 2001;Shea, Ma, Yeh, Lee, & Pituc, 2009). Moreover, a meta-analytic study indicated that the largest effects on career decision self-efficacy is a self-concept variable, i.e., self-esteem, among several personal variables (Choi et al, 2012).…”
mentioning
confidence: 93%
“…In particular, negative intra-individual variables have been linked with individuals who report significantly higher levels of career indecision (Kelly & Lee, 2002). These include a negative affective disposition (Multon, Heppner,&Lapan, 1995), anxiety (Germeijs, Verschueren, &Soenens, 2006), fear of success (Staley, 1996) and lower self-esteem (Creed,Prideaux, & Patton, 2005;Germeijs& De Boeck, 2002, 2003Staley, 1996). Saka, Gati, and Kelly (2008) explored relevant personality and emotional factors in their model, and identified three major sources of problems -pessimistic views, anxiety, and selfconcept/identity.…”
Section: Career Decision-makingmentioning
confidence: 99%
“…The general finding is that higher levels of career indecision appear to be associated with lower life satisfaction (Creed et al, 2005;Skorikov, 2007). No studies have examined how one's hope for life relates to career decisions.…”
Section: The Current Studymentioning
confidence: 99%
“…The kind of the educational and cultural context the child receives determines the kind of vocational interests a child forms all through their going to school (Watson et al, 2011). Creed et al (2005) state that the societal influence that begins from the family greatly contributes to the kind of vocational interests formed by the children. Therefore, schools have to play a critical role in positively supporting students" interests formed through the social context they live in.…”
Section: Abilitiesmentioning
confidence: 99%